Analysis Of The Regulation Of The Minister Of Law And Human Rights Number 11 Of 2020 Toward Indonesia's Capability Facing Pandemic Covid-19 - Muhammad Azzam Alfarizi; Ridha Nikmatus Syahada (Polteknik Imigrasi, 2020)
The Government of Indonesia through the Ministry of Law and Human Rights provides a policy to temporarily ban foreigners from entering Indonesian territory as stipulated in Permenkumham No. 11 of 2020. The existence of this new policy automatically invalidates previous policies related to the Granting of Visas and Stay Permits and temporary suspension of Visit Visa Free and Visit Visa on arrival and Granting of a Limited Stay Permit. The policy is a serious step taken by the government aimed at preventing the entry of the COVID-19 corona virus into Indonesian territory. So that with this policy an impact on the stability of the situation in Indonesia will emerge. Immigration is part of the government that formulated the existence of this policy, the existence of this policy is considered good in terms of its application, but it has a negative impact on the Indonesian economic sector which eventually declined to around 2.5% half of Indonesia's economic increase in 2019, namely 5%. The research uses a conceptual approach (conceptual approach), and a case approach (Case Approach). The implementation of government policies on prevention while foreigners enter Indonesia is in line with other national policies in dealing with the COVID-19 pandemic, without forgetting the effect on national economy in maintaining its stability. This policy must be supported by good supervision so that its application is able to run optimally to maintain the safety of the Indonesian people which impacts on the ability to maintain their welfare after the Pamdemic. Thus the decline of the Indonesian economy and the spread of a pandemic in the midst of society can be suppressed.